Effect of Tillage and Mulching on Growth, Yield and Economics of Maize Crops - Kumar, Pramod; Lata, Suman; Swapnil; Sinha, Anuradha; Singh, Digvijay (International Journal of Bio-resource and Stress Management, 2022)
The field experiments were conducted during July to October, 2017, 2018 and 2019 in split plot design was laid out at Zonal Research Station farm, Chianki, Palamu, Jharkhand, India. The cultural practices included two factors i.e. the first factor included conventional tillage (CT), minimum tillage (MT), raised bed sowing (RBS), the second factor included without mulch (WM), farm waste mulch (FWM), polythene mulch (PM), soil mulch (SM). The rain water use efficiency was higher in raised bed sowing+polythene mulch (5.71 kg ha-1mm-1) than the other treatments but it was lowest in MT+WM (2.96 kg ha-1 mm-1) over the three years. The high water use efficiency in the year 2019 (5.71 kg ha-1 mm-1) influences the maximum growth and yield (5,169 kg ha-1)of the crop followed by 2018 (4.74 kg ha-1 mm-1) but the minimum yield was found under minimum tillage without mulch in every year. This higher growth leads to higher stover yield and plastic mulch prevents the weeding cost which finally improved the B:C ratio (1.97) by reducing cost of cultivation and improving net return. In conclusion, minimum tillage without mulch is not recommended under dryland condition but raise bed sowing with plastic mulch is a suitable practice among all practices. This shows that raised bed practice prevent the maize crop from excess water condition and plastic mulching is helpful in increasing water use efficiency, controlling weed and maintaining temperature near root zone but no mulch condition degrade the fertile layer of soil by erosion.